IMPLEMENTASI UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG PENATAAN RUANG DALAM RANGKA MEWUJUDKAN RUANG TERBUKA HIJAU DI KOTA PEKANBARU - Afriani Rebecka Falipi; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The problem of green open space (RTH) in Pekanbaru City in particular, requires structural handling through various studies and policies considering that green open space (RTH) is an ecosystem controller and a balancer for environmental quality. The area of public green open space in Pekanbaru City is only 1,790.89 hectares (2.83%) and the area of private green open space is 8,113.49 hectares of the total city area, which is 63,226 hectares (12.83%). It can be seen that the implementation of the regulation of Law Number 26 of 2007 concerning Spatial Planning Article 29 paragraphs (1), (2) and (3) has not been realized properly or has not been maximized. Thus, the objectives of writing this thesis are: First, to find out the implementation of Law Number 26 of 2007 concerning Spatial Planning in the context of realizing Green Open Spaces in Pekanbaru City, Second, the inhibiting factors for spatial planning in realizing Green Open Spaces in Pekanbaru City, Third Efforts made by the Pekanbaru City Government in Structuring Green Open Space.This type of research can be classified in the type of sociological research, because in this study the author directly conducts research on the location or place under study in order to provide a complete and clear picture of the problem to be studied. This research was conducted at the Department of Public Works and Spatial Planning Pekanbaru City, while the population and sample are all parties related to the problems studied in this study, the data sources used are primary data and secondary data.From the results of the research problem there are three main things that can be concluded. First, the implementation of Law Number 26 of 2007 concerning Spatial Planning in the context of realizing Green Open Spaces in Pekanbaru City has not been realized properly that public green open spaces in Pekanbaru City are only 2.83% of the proportion of public green open spaces of at least 20%. And the implementation has also interfered with human rights, namely in accordance with Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Second, there are several factors that hinder spatial planning in realizing the Green Open Space. Third, there are several efforts made by the Pekanbaru City Government.Key Words : Green Open Space – Human Rights- Spatial Planning – Implementation